Pb2+-N bonding chemistry: recycling of polyaniline-pb nanocrystals waste for generating high-performance supercapacitor electrodes - Jha, Plawan Kumar; Singh, Santosh K.; Gatla, Suresh; Mathon, Olivier; Kurungot, Sreekumar; Ballav, Nirmalya (Journal of Physical Chemistry C, 2016)
Understanding of Pb-N bonding chemistry is not only fundamentally important in the view of relativistic inert-pair effect but also is important for therapeutic as well as environmental applications. In the present study, an unusual reactivity of N-containing pi-conjugated polyaniline emeraldine base (EB) toward aqueous Pb2+ ions has been identified. In the course of sequestering Pb2+ ions by EB, cuboid-shaped nanocrystals were isolated. Synchrotron-based X-ray absorption near-edge structure and extended X-ray absorption fine structure techniques were employed to understand Pb-N bonding chemistry in EB-Pb nanocrystals. The adopted methodology of slow exposure of HCl vapor to EB-Pb nanomaterial facilitated the isolation of polyaniline emeraldine-salt (ES) with unique morphological patterns, porosity and electrical conductivity. The electrochemical device based on recycled ES showed high-capacitance value (similar to 606 F/g @1 A/g and similar to 663 F/g @10 mV/s), high-energy density (similar to 14.8 Wh/kg at power density of similar to 663 W/kg) and excellent-cycling stability (only similar to 15% degradation after 1100 continued cycles at current density of 5 A/g). Notably, ES materials prepared directly from EB and upon exposing HNO3 vapor exhibited greatly inferior device performance.

High-level supercapacitive performance of chemically reduced graphene oxide - Jha, Plawan Kumar; Singh, Santosh Kumar; Kumar, Vikash; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Chem, 2017)
Reduction of graphene oxide (GO) is an important process because it holds promise for the production of reduced graphene oxide (rGO) with physicochemical properties similar to those of pristine graphene. In conventional chemical reduction, strong reducing agents, such as sodium borohydride and hydrazine, cannot be recycled. Also, fast reaction kinetics bring an imbalance in the desirable properties of rGO. Here, we present one-pot chemical reduction of GO in aqueous medium by an unconventional mild reducing agent (FeCl2/HCl) where rGOis isolated as the precipitate and the reducing agent is recycled upon simple treatment of the filtrate with HCl. The fabricated all-solid-state supercapacitors of as-synthesized rGO exhibited significantly higher specific capacitance than those obtained with rGO derived from conventional reducing agents. The cycling stability of the all-solid-state supercapacitor (> 80% retention of capacitance beyond 100,000 continued cycles) and its flexibility (> 500 bending cycles) were remarkable. Use of commercially available organic electrolyte further boosted the supercapacitor performance.

Metamagnetism in nanosheets of Co-II-MOF with T-N at 26 K and a giant hysteretic effect at 5 K - Gupta, Kriti; Dadwal, Arun; Rana, Shammi; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2018)
Herein, we have synthesized at room-temperature two-dimensional nanosheets of a MOF comprised of cobalt(II) ion with benzenedicarboxylic acid ligand, which exhibited unusual magnetic properties. Direct-current magnetic susceptibility revealed an anti-ferromagnetic (AFM) transition at 26 K (Neel temperature, T-N) followed by a canting of the spin moments along with the concomitant appearance of a sigmoidal-shaped magnetization versus field (M-H) curve at 15 K. Such a canted AFM ordering led to nonzero remnant magnetization with a remarkably high coercive field of similar to 10 kOe at 5 K. Metamagnetism was further: substantiated by the alternating-current magnetic susceptibility measurements.

Embedding S=1/2 Kagome-like lattice in reduced graphene oxide - Gupta, Kriti; Jha, Plawan Kumar; Dadwal, Arun; Debnath, Anil K.; Jaiswal, Ishan; Rana, Shammi; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry Letters, 2019)
An elegant platform to explore frustrated magnetism is the kagome spin lattice. In this work, clinoatacamite, a naturally occurring S = 1/2 kagome-like antiferromagnetic insulator, is synthesized in water at ambient pressure for the first time from a cuprous chloride (CuCl) precursor whereby Cu(I) was spontaneously oxidized to Cu(II) in the form of clinoatacamite [Cu-2(OH)(3)Cl] with a simultaneous reduction of graphene oxide (GO) to reduced graphene oxide (rGO) in one pot. A stable nanocomposite of phase-pure clinoatacamite nanocrystals embedded in the rGO matrix was isolated. The clinoatacamite-rGO nanocomposite was determined to be magnetically active with a markedly enhanced coercive field of similar to 2500 Oe at S K as well as electronically active with a conductivity value of similar to 200 S.m(-1) at 300 K. Our results illustrate an avenue of combining exotic magnetic and electronic lattices without impeding their individual characteristics and synergistically generating a new class of magnetic semiconductors.

In-situ generated Mn3O4-reduced graphene oxide nanocomposite for oxygen reduction reaction and isolated reduced graphene oxide for supercapacitor applications - Jha, Plawan Kumar; Kashyap, Varchaswal; Gupta, Kriti; Kumar, Vikash; Debnath, Anil Krishna; Roy, Debashree; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Carbon, 2019)
We have generated in situ nanocomposite of Mn3O4 and reduced graphene oxide (rGO) upon employing wet-chemical reduction of graphene oxide (GO) by Mn(II) salt as mild-reducing agent for the first time and examined the oxygen reduction reaction (ORR) activity in 0.1 M KOH electrolyte. The half-wave potential (E-1/2) of the nanocomposite catalyst (20% Mn3O4-rGO/C) was found to be around -0.153 V which is only similar to 87 mV negative from the commercially available catalyst (20% Pt/C). Remarkably, after 5000 linear sweep voltammetry cycles the E-1/2 shifted marginally by 20 mV; and the number of electrons transferred during ORR was estimated to be close to 4. Such an efficient electrocatalytic performance of the nanocomposite was primarily attributed to the synergistic interaction between Mn3O4 and rGO. The fabricated all-solid-state supercapacitor of rGO (extracted from the nanocomposite) in aqueous polyvinyl alcohol-sulfuric acid (PVA-H2SO4) gel polymer electrolyte (GPE) showed C-s value of similar to 310 F/g at a current density of 1 A/g along with long durability (10,000 charge-discharge cycles). All-solid-state flexible rGO supercapacitor exhibited high-flexibility and excellent durability (30,000 cycles with 100% retention of C-s). Our results provide an enormous opportunity in designing transition metal oxides decorated semiconducting reduced graphene oxide nanocomposite platforms for various electrochemical applications. (C) 2019 Elsevier Ltd. All rights reserved.

Exploring magnetic XY behavior in a quasi-2D anisotropic triangular lattice of Cu(II) by functionalized graphene - Gupta, Kriti; Dadwal, Arun; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2020)
Study on magnetism in two-dimensional (2D) spin-lattices is advancing rapidly. In this work, phase-pure botallackite (Bo) (Cu-2(OH)(3)Br), a quasi-2D S = 1/2 anisotropic triangular spin-lattice is stabilized over 2D reduced graphene oxide (rGO) nanosheets via simple oxidation-reduction reaction chemistry. In comparison to polycrystalline Bo, such an anchoring resulted in the oriented growth of Bo crystallites in the Bo-rGO system. The Bo-rGO nanocomposite was found to be magnetically active with a Neel transition at 8.9 K, crossing over to possible XY anisotropy at similar to 5 K-as revealed by complementary dc and ac susceptibility measurements-an unprecedented observation in the field assigned to an interfacial effect. This work demonstrates the potential usage of nonmagnetic 2D functionalized graphene to significantly modulate the magnetic properties of 2D spin-lattices.